Design of castellated steel beams - Bauer, Kyle (Kansas State University, 2021)
The goal of this report is to obtain a better understanding of the behavior and design of castellated beams. Castellated steel beams are efficient members for steel gravity systems. Steel I-beams are commonly used in steel building floors, but require large sizes for long spans. A castellated beam is fabricated by cutting W-beams in a certain pattern and welding the parts together to create a deeper section with hexagon openings in the web. Creating a castellated beam from a root I-beam increases strength and stiffness of the member and allows it to support loads at longer spans without increasing beam self-weight. Having a higher moment capacity decreases the number of beams in a bay and lowers both material and connection costs. In addition, the web openings allow integration for MEP systems by running conduits, pipes, and ductwork through the beam. Due to the web openings, castellated beams behave differently than typical I-beams. Web openings complicate the design and fabrication of castellated beams as they have additional limit states to be checked. American Institute of Steel Construction (AISC) Design Guide 31: Castellated and Cellular Beam Design (2016) provides details on how to design castellated beams. The design equations determine both global and local forces acting on castellated beams as well as unique design strength calculations. Other design strengths can be found in AISC 360 Specification for Steel Buildings. This report examines the design procedure of castellated beams and highlights the uniqueness of their design. Two design examples were presented to illustrate the design procedures, one without and one with a composite floor system.
Keywords: Design; Design Guide 31; Limit state; Castellated beam